Assessment of Drug Abuse in Iran's Prisons - Jafar Bolhari (Drug Control Headquarters, Research and Education Office, 2003)
Drugs are consumed in all prisons throughout the world in such a way that the matter has turned into a challenging issue for the governments. The current research seeks to determine the level of the spread of drug abuse among prison inmates in the country's prisons. To name the other objectives pursued by this research one can refer to the distinction of demographic features of the abusers, determining the type of drugs distributed, the method of consumption in prisons, existence of high-risk behaviors and its level among prison inmates as well as taking into consideration the spread of mental disorders along with drug abuse. Such a research has been carried out in the form of a qualitative and quantitative study. The collection of the required data in the qualitative study was conducted by using detailed questionnaires and through interviews in four groups comprising male and female inmates who have committed drug-related crimes or other offences, prison wards as well as prison authorities. In the quantitative study that was conducted on male inmates questionnaires related to demographic and general specifications, the assessment of the situation of drug abuse and individuals' view towards drug abuse as well as SCL-90-R were used. The group under study includes all prison inmates, prison wards and prison authorities in Iran. The individuals under study were selected from prisons in five different provinces using the cluster sample-taking and random methods. The number of individuals in the sample reached 1436 people. In order to clarify the outcome, frequency tables, mode, mediam, mean, standard deviation as well as X & Z tests were used. The result of the research implies that the comparison of drug abuse before and after entering the prison indicates a meaningful relationship.Meanwhile no meaningful difference was observed among age groups.